Experimental study on thermal hazard and facade flame characterization induced by incontrollable combustion of indoor energy usage. (15th September 2020) - Zhang, Xiaochun; Zhang, Zijian; Su, Guokai; Tang, Fei; Liu, Aihua; Tao, Haowen
Abstract: Fire accidents induced by indoor energy combustion occurred frequently and caused tremendous loss. This paper investigated the evolution laws of important fire risk parameters for quantitatively assessing the thermal hazard of room with triangular windows by reduced-scale experiments. The fire hazard was characterized by the risk parameters of hot gas temperature inside the room and facade flame height. Results show that the neutral plane position is hardly affected by total heat release rate of fire source, and it mainly depends on triangular opening height rather than base width. The ratios of neutral plane height above opening bottom to opening height are about 0.25, 0.25 and 0.61 for isosceles, right and inverted right triangular openings respectively. Based on theoretical derivation, an appropriate ventilation factor for triangular opening was defined to describe air mass inflow rate during under-ventilated condition. The hot gas temperature inside the room can be predicted based on the newly defined ventilation factor. Finally, a non-dimensional correlation was proposed to characterize facade flame height as a 0.53 power function of a normalized excess heat release rate. This work is of benefits to evaluate the fire hazard of buildings and then to provide calculation basis for building fire protection design. Highlights: Under-ventilated flame with triangular window induced by indoor energy was studied. Neutral plane position and air mass inflow rate was quantitatively discussed. A correlation on hot gas temperature in under-ventilated fire room was developed. The proposed non-dimensional model can well correlate facade flame height.